The Influence of Tax Knowledge and E-Filing System Implementation on MSME Tax Compliance in the Digital Economy Era (Study at KPP Pratama Cimahi) - Azzahra, Meidina; Sastradipraja, Usman (Journal of International Accounting, Taxation and Information Systems, 2025)
This study aims to measure and examine the influence of tax knowledge and the implementation of the e-filing system on tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in the digital economy era. The background of this research is the persistently low level of tax compliance among MSMEs, despite the widespread implementation of digital tax reporting systems such as e-filing. A quantitative approach with a causal associative method was employed. Primary data were collected through questionnaires distributed to MSME taxpayers registered at the Cimahi Primary Tax Office (KPP Pratama Cimahi). The data were analyzed using multiple linear regression. The results indicate that both tax knowledge and the implementation of the e-filing system have a positive and significant effect on tax compliance. These findings are expected to contribute to government and tax authorities’ efforts in improving tax compliance through education and the development of more user-friendly digital reporting systems.